Capstone senior research course in economics. Issue 2 (2nd April 2016) - Li, Ishuan; Simonson, Robert
ABSTRACT: In this article, the authors describe the structure and assessment of a capstone course in economics. The outcomes are noteworthy for three reasons. First, among cited evidence to date, this is the only undergraduate economics program from a nonselective public university reporting similar achievements in undergraduate research paper publications. Second, the program reports learning outcomes of a relatively new instrument in standardized test (ETS MFT Economics) to measure attainment of proficiencies in economics. Finally, it introduces undergraduate research paper competition outcomes as a measure of student paper quality.